Resistance of South American opossums to vWF-binding venom C-type lectins. (30th April 2020) - Drabeck, Danielle H.; Rucavado, Alexandra; Hingst-Zaher, Erika; Cruz, Yolanda P.; Dean, Antony M.; Jansa, Sharon A.
Abstract: Opossums in the clade Didelphini are well known to be resistant to snake venom due to endogenous circulating inhibitors which target metalloproteinases and phospholipases. However, the mechanisms through which these opossums cope with a variety of other damaging venom proteins are unknown. A protein involved in blood clotting (von Willebrand Factor) has been found to have undergone rapid adaptive evolution in venom-resistant opossums. This protein is a known target for a subset of snake venom C-type lectins (CTLs), which bind it and then induce it to bind platelets, causing hemostatic disruption. Several amino acid changes in vWF unique to these opossums could explain their resistance; however, experimental evidence that these changes disrupt venom CTL binding was lacking. We used platelet aggregation assays to quantify resistance to a venom-induced platelet response in two species of venom-resistant opossums ( Didelphis virginiana, Didelphis aurita ), and one venom-sensitive opossum ( Monodelphis domestica ). We found that all three species have lost nearly all their aggregation response to the venom CTLs tested. Using washed platelet assays we showed that this loss of aggregation response is not due to inhibitors in the plasma, but rather to the failure of either vWF or platelets (or both) to respond to venom CTLs. These results demonstrate the potential adaptive function of a trait previously shown to be evolving under positive selection. Surprisingly, these findings also expand the list of potentially venom tolerant species to include Monodelphis domestica and suggest that an ecological relationship between opossums and vipers may be a broader driver of adaptive evolution across South American marsupials than previously thought. Highlights: We investigate the ability of opossums to resist venom C-type lectins. We use physiological assays to isolate the source of that resistance to the vWF-Platelet-C-type lectin interaction. Large and small bodied opossums appear to be able to resist the physiological aggregation response to C-type lectins seen in susceptible mammals. vipers may be a broader driver of adaptive evolution across marsupials than previously thought.